2019
DOI: 10.1088/1755-1315/272/2/022065
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Effect of Fly Ash on Biological Environment

Abstract: Class F fly ash is non-demand mineral by-product from fuel industry that is stored in landfills polluting a surrounding territories. Content and composition of soluble mineral components in fly ashes from different power plants are varied in wide range. Leaching into fly ashes these component can differently effect on bioobject activity. In this paper correlation between pH-value of water extracts from fly-ashes, hardness of them and content of evapored mineral residue from the water extract was studied. It is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Given that fly ash is a residual material, an environmental study has been carried out to characterize the product more completely in order to make a better evaluation about its possible uses as construction materials. In particular, the influence of low-calcium fly ash products on life activities of flora and fauna has already been investigated ( Kozhukhova et al, 2019 ), observing a negative effect onto the ecosystem due to release of the ions such as Na + , Cl – , and SO 3 2– as well as CaO. Nevertheless, the use of fly ash as a major component in geopolymer binders assumes the physical–chemical encapsulation with consequent prevention of the release of toxic cations and ions into the environment ( Kozhukhova et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given that fly ash is a residual material, an environmental study has been carried out to characterize the product more completely in order to make a better evaluation about its possible uses as construction materials. In particular, the influence of low-calcium fly ash products on life activities of flora and fauna has already been investigated ( Kozhukhova et al, 2019 ), observing a negative effect onto the ecosystem due to release of the ions such as Na + , Cl – , and SO 3 2– as well as CaO. Nevertheless, the use of fly ash as a major component in geopolymer binders assumes the physical–chemical encapsulation with consequent prevention of the release of toxic cations and ions into the environment ( Kozhukhova et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Geopolymer concrete (GPC) has the advantages of environmental protection and energy savings, as well as mechanical properties close to or better than OPC concrete (OPCC) [ 16 , 17 , 18 , 19 , 20 ]. Besides, GPC will show higher temperature resistance on some structures, compared to OPCC [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, lately, some studies highlighted the environmental impact of geopolymers and their main components. The production of industrial materials, such as fly ash used in the production of geopolymer material, showed a lower rate of toxicity when compared to the production of OPC [248,249]. The use of optimization techniques for producing geopolymer materials has not been extensively studied yet.…”
mentioning
confidence: 99%